THREE-STEP INTERVIEW IN TEACHING SPEAKING - Ayu Metia Novayanti; Setya Resmini (IKIP Siliwangi, 2021)
Three-Step Interview is a cooperative learning strategy that offers an alternative to the competitive approach of whole class question-answer, in which the teacher will provide a certain topic and students may ask questions in pair. The purpose of this research is to investigate students’ difficulties on implementing Three-Step Interview in speaking. This research used descriptive qualitative method. The tenth grade of IPA 3 in one Senior High School in Cimahi which consisted of 32 students were selected as the respondents of this research. Questionnaire and interview were used in order to obtain the data. The result of this research shows that most of the students feel difficulties in linguistic aspects, included vocabulary (94%), pronunciation (56%), and grammar (88%) out of 32 students. Meanwhile, there is no significance difficulties in implementing the technique, only 44% students who find difficulties in the second step. Keywords: Three-Step Interview, Teaching Speaking, Difficulty